PENERAPAN GRAPH-COLORING UNTUK REKOMENDASI PUSAT OLEH-OLEH KHAS SAMARINDA - Amelia Yusnita; Kusnandar Kusnandar; Dewi Rosita (Direktorat Riset dan Pengabdian Pada Masyarakat (DRPM) Universitas Bina Darma, 2021)
There are too many souvenir centers in Samarinda. Usually, it makes everyone confused to choose it, and it takes a long time to decide. This is one of the most common problems. In determining the location of the souvenir center, it is necessary to use place recommendations to save time. Therefore we need a system and method that can be applied to recommend a souvenir center. The souvenir center place recommendation application is made to help everyone in finding a souvenir center place with a choice of types of souvenirs. The method used is the Graph Coloring Method; with the application development method used is Waterfall consisting of data analysis, technology analysis, system analysis, information analysis and user analysis. The result of this research is that an application for determining the souvenir center, that application ion can recommend a center for souvenirs with the same choice of souvenirs. Users can input the type of souvenirs that they want, and then the application will recommend the center of the souvenirs by using a simple row and point coloring algorithm. After processing, the application will be able to display the results of recommendations for souvenir centers with the same type of souvenirs.